Patricia L. Swier and Julia Riordan-Goncalves, eds. Dictatorships in the Hispanic World: Transatlantic and Transnational Perspectives. Madison, NJ: Fairleigh Dickinson UP, 2013 - Bécquer Seguín (Studies in 20th & 21st Century Literature, 2018)
Review of Patricia L. Swier and Julia Riordan-Goncalves, eds. Dictatorships in the Hispanic World: Transatlantic and Transnational Perspectives. Madison, NJ: Fairleigh Dickinson UP, 2013.
Keywords: Dictatorship; Hispanic Studies; Cultural Studies; Spain; Latin America; Transatlantic Studies